Salmonella enterica Subclinical Infection: Bacteriological, Serological, Pulsed-Field Gel Electrophoresis, and Antimicrobial Resistance Profiles-Longitudinal Study in a Three-Site Farrow-to-Finish Farm - Vigo, Germán B (2009)
Fil: Vigo, German B. Universidad Nacional de La Plata. Laboratorio de Diagnóstico e Investigaciones Bacteriológicas; Argentina.